Depletion of hepatic glutathione and adenosine by glucocorticoid exposure in Wistar rats is pregnancy-independent - Lawrence A. Olatunji; Olufunto O. Badmus; Kamaldeen O. Abdullahi; Taofeek O. Usman; Mary ologe; Abdullahi Adejare (Toxicology Reports, 2024)
Liver diseases have gained increasing attention due to their substantial impact on health, independently as well as in association with cardio-metabolic disorders. Studies have suggested that glutathione and adenosine assist in providing protection against oxidative stress and inflammation while glucocorticoid (GC) therapy has been associated with chronic inflammatory disorders, even in pregnancy. The implications of Glucocorticoid exposure on maternal health and fetal growth is a concern, however, the possible role of glutathione and adenosine has not been thoroughly investigated. The study therefore hypothesize that exposure to glucocorticoids leads to depletion of hepatic glutathione and adenosine levels, contributing to oxidative stress and tissue injury. Additionally, we aim to investigate whether the effects of glucocorticoids on hepatic health are pregnancy dependent in female rats. Twelve Pregnant and twelve age-matched non-pregnant rats were used for this study; an exogenous administration of glucocorticoid (Dex: 0.2 mg/kg) or vehicle (po) was administered to six pregnant and six non-pregnant rats from gestational day 14 to 19 or for a period of 6 days respectively. Data obtained showed that GC exposure led to a decrease in hepatic glucose-6-phosphate dehydrogenase, glutathione peroxidase, GSH/GSSG ratio and adenosine content in both pregnant and non-pregnant rats. In addition, increased activities of adenosine deaminase and xanthine oxidase, along with increased production of uric acid and increased levels of lactate dehydrogenase, aspartate aminotransferase, alanine transferase, alkaline phosphatase and gamma-glutamyl transferase were observed. In summary, the study indicates that GC-induced liver damage is underlined by depleted hepatic adenosine and glutathione levels as well as elevated markers of tissue inflammation and/or injury. Furthermore, the findings suggest that the effects of GC exposure on hepatic health are pregnancy independent.